Evaluation of a real-time method of simultaneous amplification and testing in diagnosis of Mycoplasma pneumoniae infection in children with pneumonia - Li, Wei; Fang, You-hong; Shen, Hong-qiang; Yang, De-hua; Shu, Qiang; Shang, Shi-qiang (PloS one, 2017)
Mycoplasma pneumoniae (M. pneumoniae) infection can cause community acquired pneumonia in children. A real-time method of simultaneous amplification and testing of M. pneumoniae (SAT-MP) was developed to diagnose M. pneumoniae targeting a region of the ribosomal RNA. The SAT-MP assay can accurately identify M. pneumoniae with a detection range from 101 to 107 CFU/ml. In this study, the specimens from 315 children with pneumonia were collected and analyzed by SAT-MP in parallel with real-time PCR method and IgM ELISA assay. The positive rates of these specimens examined by SAT-MP assay, real-time PCR method and IgM ELISA assay were 16.51%, 15.56% and 12.70% respectively. While there was statistical significance (p = 0.04) between SAT-MP assay and IgM ELISA assay, no statistical significance (p = 0.25) was found between SAT-MP assay and real-time PCR method and these two methods had high consistency (kappa value = 0.97). These findings indicate that the newly developed SAT-MP assay is a rapid, sensitive and specific method for identifying M. pneumoniae with potential clinical application in the early diagnosis of M. pneumoniae infection.